Analisis Isi Jurnal Ilmiah Pendidikan Agama Islam: Studi Bibliometrik - St. Wardah Hanafie Das; Zamri Zamri; Hasmi Hasmi; Hasnita Hasnita; Jamaluddin Hanapi (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
This study aims to analyze the development of scientific studies in Islamic Religious Education (PAI) through a bibliometric study approach. Bibliometric studies are used to map research trends, publication productivity, study focus, and authorship patterns in Islamic Religious Education (PAI) scientific journals. Research data was obtained from PAI journal articles published within a specific year and indexed nationally and internationally. Data collection techniques were conducted through electronic journal database searches using relevant keywords. Data analysis included the number of publications per year, dominant research themes, research methods used, and author collaborations. The results show a significant increase in publications in Islamic Religious Education (PAI) journals, with dominant themes including character education, values-based learning, religious moderation, and technology integration in Islamic Religious Education (PAI) learning. The most commonly used research methods are descriptive qualitative and literature studies, while quantitative and experimental research remains relatively limited. Authorship patterns are dominated by single authors and two-author collaborations, indicating the need for increased academic collaboration across institutions. This study contributes to understanding the direction of Islamic Religious Education (PAI) research development and serves as a basis for developing further research to be more innovative and oriented towards contemporary educational needs.